Bladder Dysfunction in a New Mutant Mouse Model With Increased Superoxide—Lack of Nitric Oxide? - Soler, Roberto (2010)
PURPOSE: Nitric oxide mediates urethral smooth muscle relaxation and may also be involved in detrusor activity control. Mice with mutation in the Immp2l gene have high superoxide ion levels and a consequent decrease in the bioavailable amount of nitric oxide. We studied bladder function in this mouse model. MATERIAL AND METHODS: Young male mutants at ages 4 to 6 months, old female mutants at age 18 months and healthy WT age matched controls were used. The detrusor contractile response to carbachol and electrical field stimulation was tested in isolated detrusor strips in organ baths. In vivo bladder function was evaluated by cystometry in conscious animals. RESULTS: Young male mutants had significantly lower micturition and higher post-void residual volume than WT controls. They had pronounced voiding difficulty and strained when initiating micturition. Detrusor contractile responses to carbachol and electrical field stimulation were similar in mutant and WT mice. Old female mutant mice had lower bladder capacity and micturition volume, and higher micturition frequency and bladder-to-body weight ratio than WT controls. In the in vitro study detrusor strips from mutants showed a lower maximum response to carbachol. CONCLUSIONS: Mice with mutation in the Immp2l gene have bladder dysfunction, mainly characterized by emptying abnormalities in young males and increased detrusor activity in old females. Detrusor function was preserved in young males and impaired in old females. These animals are a natural model of oxidative stress with low bioavailable nitric oxide. Thus, they are interesting tools in which to evaluate the role of these conditions on bladder dysfunction.